Patterns and attributes in vulnerable children's messy play. Issue 2 (4th March 2017) - Gascoyne, Sue
ABSTRACT: 'Messy play' is often viewed as a purely ludic play activity in early childhood settings, however, some professionals in therapeutic contexts have understood it as potentially significant for supporting young children who have experienced trauma. This article reports on a study that explored how young children who have experienced trauma may use their engagements in messy play to regulate and express their emotions. Children's uses of messy play resources in a therapeutic environment were observed. The resources included sand, water, paint, playdough, gloop, gellybaff, clay, shredded paper and shaving foam. When the children used these resources, patterns, special attributes and transformative qualities in their interactions with them were captured. This revealed that the children used messy play as a conduit for communication. Findings from the study were identified as potentially useful for practitioners working in mainstream early childhood settings.